KAJIAN PUPUK KANDANG TERHADAP INTENSITAS PENYAKIT BERCAK COKLAT SEMPIT (Cercospora oryzae) PADA TANAMAN PADI KETAN PUTIH (Oryzae sativa L. Glutinosa) - Atmaja, Rachmayani Ayu Wira; Santosa, Sartono Joko; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
This research entitled Study of Manure on the intensity of Narrow Brown Spot (Cercospora oryzae) on White Glutinous Rice Plants(Oryza sativa L. Glutinosa) with the aim to examine the effect of manure on the intensity of narrow brown spots (Cercospora Oryzae) on white glutinous rice plants. Have been done from 29 October 2019 to 3 March 2020, in the Village of Donohudan, Ngemplak District, Boyolali Regency, Central Java, with an altitude of 150 (masl). This research usedthe method a Randomized Complete Block Design (RCBD) with a single factor consisting of 10 kinds of treatments and repeated 3 times. The combination of treatments as follows: D0, A1, A2, A3, K1, K2, K3, S1, S2, S3. The data of this research were analyzed with the HSD test (Honestly Significant Difference) at 5% significance level, while the results of the research showed that symptom of attacks narrow brown spot (Cercospora oryzae) first appear at the age of 30 days after planting in thr treatment of cow manure, while narrow brown spot (Cercospora oryzae) evenly distributed at the age of 40 days after planting in the treatment of chicken manure and goat manure. Chicken manure with a dose of 4,5 kg/plot could suppress the intensity of narrow brown spot (Cercospora oryzae) disease on the leaves and narrow brown spot (Cercospora oryzae) on the leaves, and the use chicken manure with a dose of 4,5 kg/plot give the highest yield in grain weight per plot is1820,90 grams and significantly affect the control treatment or without the provision of manure (an increase of 38,73%) but did not significantly affect the treatment of goat manure and cow manure.